2008
DOI: 10.1111/j.1399-5448.2008.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors of poor metabolic control in type 1 diabetic children assisted in a public hospital in Argentina

Abstract: This study showed that socioeconomic and familial factors were strongly associated with metabolic control, and they will allow us to make an early detection of those patients who are more susceptible of having poor progression of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 25 publications
4
28
1
1
Order By: Relevance
“…Professional fathers have children with good glycemic control. Those findings are consistent with previous studies using the same method of our data collection, which have also proved that lower socioeconomic status which mainly results from unemployment of parents is related with higher HbA1c [12][13][14][15]. In contrast and according to the results of this study, neither mothers' educational level nor their occupational status have shown significant influence on their children glycemic control.…”
Section: Discussioncontrasting
confidence: 35%
“…Professional fathers have children with good glycemic control. Those findings are consistent with previous studies using the same method of our data collection, which have also proved that lower socioeconomic status which mainly results from unemployment of parents is related with higher HbA1c [12][13][14][15]. In contrast and according to the results of this study, neither mothers' educational level nor their occupational status have shown significant influence on their children glycemic control.…”
Section: Discussioncontrasting
confidence: 35%
“…Other studies have also found correlations of glycemic control and household composition, with improved control in those patients whose parents are married and living together vs. single‐parent households . In our study, after regression analysis, there was no significant difference in the rate of single‐parent household between the officer and enlisted groups.…”
Section: Discussionsupporting
confidence: 48%
“…The primary role of education in predicting major cardiovascular and renal events makes logical sense, as type 1 diabetes requires a large amount of self-care, and diabetes education clearly improves glycemic control. (23) However, we cannot fully explain why income is the primary SES measure associated with AN and LEAD, as these are also more prevalent with poor glycemic control. Likewise, PR was not associated with any SES measure, perhaps due to the high overall prevalence of PR in this cohort (>60%).…”
Section: Discussionmentioning
confidence: 93%